2006
DOI: 10.1590/s1516-84842006000200011
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of HTLV-infection among blood donors in Salvador, Bahia, Brazil - associated risk factors and trend towards declining prevalence

Abstract: Previous data suggest that Salvador, the capital of the State of Bahia, a northeastern state of Brazil, has the highest prevalence of HTLV infection in blood donors among Brazilian cities. The aim of this case-control study was to identify the determinants of risk for HTLV infection among blood donors in the city of Salvador. Between January 2000 and December 2003, 504 blood donors with positive screening tests for HTLV infection (unconfirmed prevalence of 0.48%) were invited to participate in our study. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
4
22
0
2
Order By: Relevance
“…A study conducted in the State of Bahia in 2006 by Mota et al showed a prevalence of 0.5% in blood donors 4 . This prevalence was lower than that determined in 1993 by the same group (1.4%), showing a significant decline over this period 5 .…”
Section: Article/artigomentioning
confidence: 99%
“…A study conducted in the State of Bahia in 2006 by Mota et al showed a prevalence of 0.5% in blood donors 4 . This prevalence was lower than that determined in 1993 by the same group (1.4%), showing a significant decline over this period 5 .…”
Section: Article/artigomentioning
confidence: 99%
“…[1][2][3] The HTLV-1 infection is endemic in Japan and several countries in South America, Caribbean and Africa. 2,[4][5][6][7] The transmission pathways of HTLV-1 infection include vertical, parenteral and sexual transmission. 2,7 Risk factors associated with HTLV-1 infection include: hemotransfusion, low socioeconomic status, low education level, high-risk sexual behavior, anal sex, fi rst sexual relationship before 18 year-old and having more than 3 sexual partners in life.…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7] The transmission pathways of HTLV-1 infection include vertical, parenteral and sexual transmission. 2,7 Risk factors associated with HTLV-1 infection include: hemotransfusion, low socioeconomic status, low education level, high-risk sexual behavior, anal sex, fi rst sexual relationship before 18 year-old and having more than 3 sexual partners in life. 7,8 Several studies have been evidencing association between HTLV-1 infection and endocrinopathies and other metabolic disorders such as autoimmune thyroid diseases, hypercalcemia, type 1 diabetes mellitus and pseudohypoparathyroidism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros estudos mostram prevalência de infecção pelo HTLV, através da técnica do WB, de 0,07% em Maringá-PR (entre 2003 e 2006) 23 , 0,11% em Rio Branco-AC (entre 1998 e 2001) 24 e 0,3% no interior da Bahia (década de 90) 25 , sendo a Bahia o estado com maiores índices de prevalência 1,26 .…”
unclassified